2008
DOI: 10.1104/pp.108.116285
|View full text |Cite
|
Sign up to set email alerts
|

Starch Biosynthetic Enzymes from Developing Maize Endosperm Associate in Multisubunit Complexes

Abstract: (F.L., I.J.T., M.J.E.)Mutations affecting specific starch biosynthetic enzymes commonly have pleiotropic effects on other enzymes in the same metabolic pathway. Such genetic evidence indicates functional relationships between components of the starch biosynthetic system, including starch synthases (SSs), starch branching enzymes (BEs), and starch debranching enzymes; however, the molecular explanation for these functional interactions is not known. One possibility is that specific SSs, BEs, and/or starch debra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
200
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 192 publications
(210 citation statements)
references
References 42 publications
9
200
0
1
Order By: Relevance
“…Nevertheless, it should be kept in mind that the transcript levels are not always related to their enzymatic activities or protein levels, considering post-transcriptional and posttranslational controls (Sun et al 2005). There are intricate functional interactions between components of the starch biosynthetic system during wheat endosperm, and the starch-biosynthesizing system in higher plants demands the concerted expression of many genes at any particular developmental stage of a particular tissue (Tetlow et al 2004;Ohdan et al 2005;Hennen-Bierwagen et al 2008). In addition to maintaining the activity levels of individual enzymes, several combinations of protein-protein interactions, such as those among the wheat proteins for SBEI, SBEIIb, and DBE might play an essential role in the metabolic regulation of starch biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it should be kept in mind that the transcript levels are not always related to their enzymatic activities or protein levels, considering post-transcriptional and posttranslational controls (Sun et al 2005). There are intricate functional interactions between components of the starch biosynthetic system during wheat endosperm, and the starch-biosynthesizing system in higher plants demands the concerted expression of many genes at any particular developmental stage of a particular tissue (Tetlow et al 2004;Ohdan et al 2005;Hennen-Bierwagen et al 2008). In addition to maintaining the activity levels of individual enzymes, several combinations of protein-protein interactions, such as those among the wheat proteins for SBEI, SBEIIb, and DBE might play an essential role in the metabolic regulation of starch biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…All plant varieties were grown in the field at ShiHeZi University, Shihezi, China, in March, 2007-2008 growing season. Crop management was the same as the local high-yield cultivation.…”
Section: Plant Materials Growth and Grains Collectionsmentioning
confidence: 99%
“…Studies with wheat and maize amyloplasts have shown that all SBE isoforms can be phosphorylated (8,9) and that protein phosphorylation regulates the association of SBE and SS isoforms in multienzyme protein complexes (see below; refs. 9,68,69).…”
Section: Regulation Of Sbes By Protein Phosphorylationmentioning
confidence: 99%
“…There is evidence that several starch biosynthetic enzymes depend on other biosynthetic components for their activity; for example, a mutation affecting SSIII reduces the activity of SBEIIa whilst also increasing the activity of SSI in cell extracts [125], indicating that starch biosynthesis is most likely to be the result of several enzymes acting in a coordinated manner. The physical and biochemical interactions between starch-synthesising enzymes must thus be taken into account in order to fully understand the process of starch biosynthesis.…”
Section: Enzyme Complexesmentioning
confidence: 99%
“…According to the specificities of individual isozymes, this complex was proposed to contribute to the synthesis of short and intermediate amylopectin branches to form the crystalline lamellae [127,130]. In addition, maize SSI, SSIIa, SSIII, SBEI, SBEIIa and SBEIIb (SSIIa, SSIII, SBEIIa, SBEIIb in ~600 kDa complex; SSIIa, SBEIIa, SBEIIb in ~300kDa complex) were found within protein-protein complexes [125]. A larger protein complex including SSIIa, SSIIIa, SSIVb, SBEI, SBEIIb and PUL (>700 kDa) was eluted by gel filtration chromatography from soluble rice endosperm extracts [131].…”
Section: Enzyme Complexesmentioning
confidence: 99%